Relationships of Forest Biodiversity and Rattan Jernang (Daemonorops draco) sustainable harvesting by Anak Dalam tribe in Jambi, Sumatra - ANDRIO ADIWIBOWO; IIK SRI SULASMI; NISYAWATI NISYAWATI (Society for Indonesian Biodiversity, 2012)
Adiwibowo A, Sulasmi IS, Nisyawati. 2012. Relationships of forest biodiversity and Rattan Jernang (Daemonorops draco) sustainable harvesting by Anak Dalam tribe in Jambi, Sumatra. Biodiversitas 13: 46-51. Conservation of tropical trees can be achieved if supported by the sustainable use of forest by community live nearby through harvesting of non timber woods, for instance rattan. Furthermore, rattan jernang individuals and trees have significant associations. Therefore, objective of this paper is to investigate the utilization of rattan jernang (Daemonorops draco Wild) related to the forest tree biodiversity by Anak Dalam tribe in several villages in Jambi, Sumatra. The study has identified that populations of Daemonorops draco were varied among villages, ranged from 40 to 71 clumps inthe forests and up to 500 clumps in plantations. Moreover, 73 individual trees consisted of 32 species were identified as rattan host and conserved by the community. Dialium platyespalyum. Quercus elmeri, and Adinandra dumosa were rattan host trees with the highest populations. Meanwhile, a biodiversity of non-host trees consisted of 30 individual trees from 16 species. Interviews revealed that traditional harvesters have acknowledged that trees have significant important ecological roles for the rattan livelihood and therefore it is very important to conserve the forests for the sustainability of harvest in the future. Furthermore, to secure the availability of rattan, thetraditional harvesters had started rattan plantation.